Lisbon's COVID 19 response: harm reduction interventions for people who use alcohol and other drugs in emergency shelters - Ricardo Fuertes; Elsa Belo; Cristiana Merendeiro; Adriana Curado; Diana Gautier; Ana Neto; Hannah Taylor (BMC, 2021)
Abstract Four emergency shelters were instituted in Lisbon during COVID-19, and are still in operation. Between March and August 2020, they served over 600 people. The shelters host a diverse population, including people experiencing homelessness, foreigners, LGBTI + people, those with reduced mobility, couples, those with pets, and People Who Use Drugs, including alcohol (henceforth PWUD). Individuals are provided care regardless of their immigration or residence status. In order to ensure continuity of care in the shelters and to bring in clients who usually refuse to be sheltered, a range of social and health interventions are integrated into the shelters. Harm reduction services ensure that the most vulnerable populations, PWUD and people experiencing homelessness, have access to the services they need. Innovations in service provision maximize the services impacts and pave the way for the future inclusion and development of these services.